Parcs à thème : paysages aménagés et paysages extérieurs. Regards croisés entre le Disneyland Park (États-Unis) et les parcs Mirapolis et Astérix (France) - Steven Damerval (Bulletin de l’Association de Géographes Français)
This article surveys the integration of theme parks into their surroundings, specifically focusing on the first two French national theme parks to be built near Paris in response to the success of Disneyland Park (Anaheim, USA): Mirapolis Park and Asterix Park. By considering the landscaping practices of Disneyland Park (Anaheim, USA) as a model, we will analyze the landscaping strategies of theme parks regarding their external landscapes and how their design either opens or closes the park to the outside world, addressing the conceptual stakes of these places, namely immersion or disorientation.